A Grammar of Bisaya in Davao - Cooke, Mary Jane A; Lovitos, Ana Helena R (Yayasan Sembilan Pemuda Indonesia, 2023)
This research presents a detailed linguistic description of the Bisaya in Davao language based on the examination of Basic Linguistic Theory. Three primary language consultants are native speakers of the language who translated and recorded word and sentence lists for accurate pronunciation. The analysis reveals the language's phonological, morphological, syntactic, and morphosyntactic characteristics. Based on the translated eliciting materials spoken and pronounced by the language consultants, there are three vowels and sixteen consonants in the phonemic inventory. Distinct phonological characteristics such as minimal pairs, diphthongs, and phonotactics are readily apparent. It demonstrates that the language has morphological characteristics and follows ergative-absolutive and verb Initial structure, precisely like other Austronesian languages in the Philippines. This description provides actual language documentation, additional research on language contact or migration, linguistic typology, and crosslinguistic study. This is vital for students and teachers in DepEd Davao in teaching the Bisaya in Davao as a mother tongue.